2008
DOI: 10.1371/journal.pone.0002452
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Pathways in COS-7 Cells Mediate Defective Internalization and Intracellular Routing of Truncated G-CSFR Forms in SCN/AML

Abstract: BackgroundExpression of truncated G-CSFR forms in patients with SCN/AML induces hyperproliferation and prolonged cell survival. Previously, we showed that ligand internalization is delayed and degradation of truncated G-CSFR forms is defective in patients with SCN/AML.Methodology/Principal FindingsIn this study, we investigated the potential roles of dileucine and tyrosine-based motifs within the cytoplasmic domain of the G-CSFR in modulating ligand/receptor internalization. Using standard binding assays with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Inactivating the Stat5 signal is associated with receptor internalization and SOCS3 suppression (19,30). In our study, we observed a prolonged Stat5 activation in the G-CSFRIV + HSPCs.…”
Section: Discussionsupporting
confidence: 60%
“…Inactivating the Stat5 signal is associated with receptor internalization and SOCS3 suppression (19,30). In our study, we observed a prolonged Stat5 activation in the G-CSFRIV + HSPCs.…”
Section: Discussionsupporting
confidence: 60%
“…[D/E] XXX [L/I[L/I]] and [D/E]XXLL) seen in LIFR [ 132 ] and IL-2Rβ [ 133 ]), and the tyrosine-based motifs (i.e. YXXϕ), promoting clathrin-dependent endocytosis and internalization, first identified in the TPOR (YRRL) and later in the G-CSFR [ 134 , 135 ]. Additionally, phosphorylation dependent degrons (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these are frequent and are well- in LIFR [127] and IL-2Rb [128], and the tyrosine-based motifs (i.e. YXXf), promoting clathrindependent endocytosis and internalization, first identified in the TPOR (YRRL) and later in the G-CSFR [129,130]. Additionally, phosphorylation dependent degrons (i.e.…”
Section: Short Linear Motifs Allow Expansion Of the Interactomementioning
confidence: 99%